Mistuning detection and onset asynchrony in harmonic complexes in Mongolian gerbils. - Klinge, A; Klump, G (2010)
By applying a Go/NoGo paradigm, thresholds for detecting mistuning of components of a 200 Hz complex were determined in the Mongolian gerbil and compared with thresholds obtained in a previous study with an 800 Hz complex. Frequency difference limens (FDLs) for detecting mistuning decreased with increasing harmonic frequency and harmonic number (0.5% to 0.01% Weber fraction). It was furthermore examined how starting and ending the mistuned component earlier than the remaining complex affects the FDL (duration of all components 400 ms, time shift 30 to 500 ms). Large FDLs that are similar to pure tone FDLs (between 21% and 6.7%) were found for onset asynchronies of 300 ms and more, indicating separate processing of the mistuned component. Small FDLs that are similar to FDLs of the synchronous condition were found if the temporal overlap between the mistuned component and the remaining complex was 100 ms or more. These experimental data in combination with a simulation of processing of the harmonic complexes by the gerbil's peripheral auditory filters led to the conclusion that the phase and amplitude modulations in the filter outputs can provide cues that allow gerbils a sensitive detection of mistuning across a wide range of frequencies.